FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KORUPSI PEMERINTAH DAERAH INDONESIA: PENEGAKAN HUKUM SEBAGAI VARIABEL MODERASI - Fani Marlina Nasution (2022)
This research is a quantitative study conducted to test and prove the relationship between the effect of fiscal decentralization, internal government audit and audit opinion on the level of corruption in the Indonesian Regional Government with law enforcement as a moderating variable. This research focuses on local governments, namely districts or cities in Indonesia in the 2020 observation period. The sample in this study is 93 data samples selected by the purposive sampling method with the criteria for district or city governments that have permanent legal corruption cases in 2020. Testing The hypothesis in this study uses Moderated Regression Analysis (MRA) with SPSS version 26 program. The results show that fiscal decentralization has a significant negative effect on the level of corruption, government internal audit has a significant positive effect on the level of corruption, audit opinion has no significant effect on the level of corruption. Law enforcement moderates the effect of government internal audit on corruption levels. Law enforcement does not moderate the effect of fiscal decentralization and audit opinion on the level of corruption.